Adaptive Neuro Fuzzy Inference System for Prediction: a Study Approach - Hafni Sahir, Syafrida; Minan, Kersna; Samsudin, S; Zufria, Ilka; Rahim, Robbi (International Journal of Engineering and Technology, 2018)
Prediction is a process of systematically estimating something that is most likely to happen in the future, based on past information and current information held, so that the difference between something that happens and the expected result can be minimized. Prediction does not have to give a definite answer to the event that will occur, but trying to find the answer as closely as possible that will happen. The ANFIS (Adaptive Neuro Fuzzy Inference System) method is a functionally similar method to the fuzzy rule base of the Sugeno model, as well as the neural network with radial functions with few restrictions that can be used to predict certain data. Â Â